Standardized mortality according to cauSe of death, age, and gender in a mining community in Northern Chile, 2006-2015 - Leyton-Hernández, Álvaro; Ramírez-Santana, Muriel (Revista Chilena de Salud Pública, 2020)
Introduction: The Chilean municipality of Andacollo was declared to be a Saturated Zone due to air pollution in 2009. It is unknown if this contamination affects the health of its inhabitants. Objective: To compare the general mortality and specific cardiovascular, respiratory, and neoplastic mortality rates in Andacollo with the national mortality rates between the years 2006 and 2015. Materials and methods: General and specific mortality rates, by gender, were calculated using official death and population registries. The Andacollo mortality rates were directly standardized by age and then compared with the national rates. Results: The adjusted mortality rates of Andacollo tend to be, on average, 20% higher than the national ones, throughout the decade. This difference is mainly due to an increased risk of dying among men, which is 35% higher for cancers, 40% higher for cardiovascular diseases, and 50% higher for respiratory diseases. These differences in risk of dying are much lower for women (average 9%) and are not observed in the younger population (20-59 years of age). Conclusions: Andacollo’s general and specific mortality rates are significantly higher than national ones, and the influence of environmental conditions on the population’s risk of dying can be ruled out, given the heterogeneity presented by sex. The excess risk of death among older men could be explained by previous occupational exposures.